Economic assimiliation of immigrants arriving from highly developed countries: The case of German immigrants in Sweden and the US - Yitchak Haberfeld; Debora Pricila Birgier; Christer Lundh; Erik Elldér (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2017)
Migration across well-developed countries has been overlooked in the immigration literature. The present study is designed to evaluate the interplay between the effects of host countries' characteristics and self-selection patterns of immigrants from a highly developed country on their economic assimilation in other developed countries. We focus on immigrants originated from Germany during 1990-2000 who migrated to Sweden and the US. We use the 5 percent 2000 Public Use Microdata files (PUMS) of the US census and a pooled file of the 2005-2007 American Community Survey, and the 2000 and 2006 Swedish Registers. We analyze eight groups of German immigrants - by country of destination (the US/ Sweden), gender, and skill level (with/without an academic degree). The results show that almost all German immigrants reached full earnings assimilation with natives of similar observed attributes, and that the assimilation of highly skilled Germans was better than that of the low skilled. We also found that the skilled immigrants were compensated for their human capital acquired in Germany prior to their migration. Finally, we find that despite higher educational levels of the Germans that headed to Sweden, the better assimilation of German immigrants, especially the highly educated, took place in the US. The better assimilation of Germans in the US was probably the result of an interaction between the Germans' pattern of self-selection (mainly on un-observed attributes) and the US context of reception - mainly higher returns on their observed human capital in the US.
Keywords: J15; J16; J18; J24; J31; J44; 330; Highly-skilled immigrants; immigrants' self-selection; immigrants' economic assimilation; highly-developed source countries